Intervensi Pemupukan dan Mikroba terhadap Pertumbuhan, Produksi, dan Mutu Benih Padi IPB 3S di Lahan Rawa Lebak - Wijaya, Aldi Kamal; Surahman, Memen; Qadir, Abdul; Giyanto, Giyanto (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Swamp land ecology is a potential land to increase the crop production, especially rice. The research was aimed to increase the production and seed quality of IPB 3S rice variety in swamp land ecology. The research was arranged in Factorial Randomized Complete Block Design with three replications. The first factor was dose of Zinc, consist of 0 kg ha-1, 15 kg ha-1, 30 kg ha-1, and 45 kg ha-1. The second factor was seed treatment by probiotic microbial, consist of control, Bacillus sp, Bacillus sp (+), Chromobacterium sp, Chromobacterium sp (+). Zinc fertilization couldn’t increase the yield characters and seed quality of IPB 3S rice variety. Microbia fertilization could increase the highest yield characters (plant height, tillers, productive tillers, panicle length, weiht per plant, and seed weight per grove), and Bacillus microbial increased the seed quality (Vigor index). Interaction of zinc fertilization (15 kg ha-1) and Chromobacterium increased the yield characters (flag leaf length, panicle length, and seed weight per grove), and the interaction of zink fertilization (30 kg ha-1) and Bacillus increased seed quality (vigour index).